Effects of 8 weeks functional training program on posture control and functional mobility in spastic hemiplegic cerebral palsy - Gulzar, Aeysha; Misbah Waris; Qurat Ul Ain (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the impacts of functional training versus conventional training on posture control and functional mobility in spastic hemiplegic cerebral palsy children. Method: The randomised clinical trial was conducted at the Rehab Cure physiotherapy centre, Lahore, Pakistan, from January to September 2020, and comprised children of either gender aged 4-14 years, diagnosed with cerebral palsy, gross motor functional classification system level II or III, and no mental retardation. The subjects were randomised into conventional therapy group A and functional training group B. Intensity of exercises was gradually increased each week, staring from 10 reps to 20 reps. The subjects received treatment 3 times a week for 8 weeks, and each session lasted 45-60 min. Paediatric Balance Scale, Trunk Control Measurement Scale, Five Times Sit to Stand Test and Timed-Up-and-Go test were used at baseline and post-intervention. Data was analysed using SPSS 21. Results: Of the 14 subjects, there were 7(50%) in each of the two groups. Overall, there were 8(57.14%) males and 6(42.86%) females with a mean age of 7.57±1.86 years. Significant improvement was noted in both groups post-intervention (p<0.05), but intergroup differences were not significant (p>0.05). Conclusion: Both functional training and conventional therapy significantly improved postural control and functional mobility in spastic cerebral palsy children, but intergroup differences were not significant. Clinical Trial Number: IRCT20200909048676N1 Key Words: Cerebral palsy, Exercises, Posture control.